An empirical study of the distribution of earthquakes with respect to rock type and depth. Issue 18 (18th September 2015) - Tal, Yuval; Hager, Bradford H.
Abstract Whether fault slip occurs seismically or aseismically depends on the frictional properties of the fault, which might be expected to depend on rock type and depth, as well as other factors. To examine the effect of rock type and depth on the distribution of earthquakes, we compare geologic models of the San Francisco Bay and the Southern California regions to the distribution of seismicity. We normalize the number of earthquakes within each rock type and depth interval by the corresponding volume to determine the earthquake density. Earthquake density is determined primarily by depth, while whether the rock is sedimentary or basement has only a secondary, depth‐dependent effect on the earthquake density. At very shallow depths, there is no difference in earthquake density between sedimentary and basement rocks. The earthquake density of basement rocks increases with depth more rapidly than that of sedimentary rocks to a similar but shallower maximum.